Melatonin - a verified remedy for jet lag? Current state of knowledge - Maciej Rogala; Kamila Giżewska; Michał Kuc; Klaudia Jabłońska; Tomasz Łoś; Karol Lorenc; Olga Bielawska; Marta Gulbicka (Kazimierz Wielki University, 2023)
Jet lag is a circadian rhythm disorder, affecting plane passengers travelling across multiple time zones. The severity of symptoms is strictly connected with the number of zones crossed. Common symptoms include: insomnia, difficulty concentrating attention, memory loss, anxiety, diarrhea, confusion, dizziness, headache, as well as malaise. Melatonin is a neurohormone, produced by the pineal gland. The hormone is released into the bloodstream and acts on MT1 and MT2 receptors, having the ability to induce sleep. Melatonin is therefore responsible for regulating the human biological clock and, consequently, the rhythm of sleep and wakefulness. Synthetic forms of melatonin have become a potential medication for various circadian rhythm disorders, including jet lag syndrome. Ten scientific reports were analyzed. The characteristics of the subjects, directions of the trips taken, the doses of melatonin, as well as the patterns of its administration, differed among studies. According to most of the reviewed trials, melatonin may have a beneficial effect on alleviating jet lag symptoms. The timing of intake plays a significant role - it has proven most effective when taken days before travel. However, several studies have not confirmed its effectiveness, compared to placebo. Further research seems to be inevitable to objectively reassess the effectiveness of melatonin preparations. Unambiguous determination of the melatonin dosage, the timing of its administration, the time of initiation, and the duration of the treatment would also be advisable. Nevertheless, all of the mentioned trials confirmed that the use of oral melatonin preparations, especially at low doses, turned out to be free of serious side effects.